Social areas in Dublin - Hourihan, Kevin (Economic & Social Studies, 1978)
The primary purpose of the paper is not to examine Dublin's factorial ecology (even with different variables and methods), but rather to identify social areas in the city and examine their interrelationships and implications. Analysis at the ward level does not allow investigation of small scale, local variations, and the use of census data is inevitably limited, so the areas identified are very much aggregate statistical regions of broad social homogeneity. On the other hand, it can be argued that such areas are the smallest feasible zones for which different plans might be formulated. Smaller areas invariably introduce elements of culture and locality, and complicate such issues as class, housing conditions and demographic structure on which regional policies within a city might be based.
Keywords: Dublin - Social analysis